Baden, Kostolac, Vučedol and Vinkovci The Late Eneolithic, Transition Period, and Early Bronze Age in the Carpathian Basin and the Western Balkans - Brnić; Želimir (Karolinum, 2023)
The book treats three primary themes. The first covers the Baden, Kostolac/Bošáca and Vučedol cultures, demonstrating their genetic relationship and indigenous development. This development is marked by changes in distribution (the global horizontal stratigraphy) caused by the penetration of the Pit Grave Culture, our second theme. The third theme analyses the emergence of the EBA. Particular attention is afforded to the absolute chronology. Two excursuses discuss finds outside the Carpathian Basin, but part of its cultural sphere. The archaeological analysis of the cultures underpins a novel cultural and historical interpretation.
Keywords: Ostatní